Sorveglianti e custodi nei testi di Ebla, fra lessico e prosopografia - Amalia Catagnoti (Asia Anteriore Antica)
The article focuses on the attestations of the Sumerograms en-nun-ak and igi-sig in the Ebla texts. Confirming that the two terms indicate activities of surveillance and custody, the discussion of various prosopographical and lexical matters permits to distinguish their different uses, as names of functions and, in the case of igi-sig, as qualification of prized goods kept in important buildings and places. Furthermore, the gathered materials can be added to those of other investigations on further personnel in charge of guard functions, in view of a comprehensive evaluation of watching activities at the time of the Palace G texts.